Generational Trauma on Motherhood in Ashley Audrain's Novel The Push (2021) (English Language and Literature (JELL), 2026)
Ashley Audrain's novel, "The Push" (2021), offers a chilling yet engaging representation of motherhood that passes trauma across generations. In this work, a qualitative assessment of literary elements will highlight the representation of trauma across iterations for the main character in her role as a mother and her ways to cope with trauma inherited within her family. With feminist theory in literature and trauma studies, a thorough analysis of plot, setting, conflict, and characterization will illustrate how trauma transcends generations of women in the family. "The Push" challenges the perspective on motherhood by how the main character deals with generational trauma in her family, using the methods mentioned in the results.
Keywords: generational trauma, motherhood, feminist literary theory, trauma studies, The Push